(untitled) (Medical Forum Monthly, 2021)
Objective: To establish the association between blood lipid levels and smoking and to develop the dose-dependent relationship between smoking habits and dyslipidemia. Study design: An analytical cross-sectional study. Place and duration of study: This study was conducted at the Cardiology Department of Ch. Pervaiz Elahi Institute of Cardiology Multan from May 2020 to October 2020 for a period of six months. Methodology: A total of 150 participants were included in the study who were divided into three groups: smokers, non-smokers, and former smokers based on their responses to the self-designed questionnaire. Additionally, the participants were investigated about their economic situation and physical activity to predict confounding variables. The blood sample of all the participants was then collected and serum levels of high-density lipoprotein, low-density lipoprotein, cholesterol, and triglycerides were measured. Results: Among the participants, 80 (53.3%) were currently smoking while the lifetime prevalence was 86.3%. Dyslipidemia was significantly greater in smokers (55.1%) than non-smokers (37%) or formal smokers (43%). The majority of smokers (42, 52.5%) were within the age bracket of 40-50 and largely belonged to the lower class (39, 48.7%) and reported moderate physical activity, in terms of MET (41, 51.25%). As for dose-response association, the significant association developed between no of cigarettes and blood High-density lipoprotein and triglycerides level in current smokers while in former smokers risk was high for high-density lipoprotein [OR, CI (1.85, 0.7-1.2)], low-density lipoprotein (1.47, 1.2-2.9), and cholesterol (1.22, 0.9-1.7). Conclusion: It is concluded that smoking significantly disturbs the body level of lipids. Moreover, the smoking dose holds a variable relationship with the different components of the blood lipid profile